2014
DOI: 10.1186/1472-6882-14-123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methanol extract of Dicranopteris linearis against carbon tetrachloride- induced acute liver injury in rats

Abstract: BackgroundDicranopteris linearis (family Gleicheniaceae) has been reported to possess anti-inflammatory and antioxidant activities but no attempt has been made to study its hepatoprotective potential. The aim of the present study was to determine the hepatoprotective effect of methanol extracts of D. linearis (MEDL) against carbon tetrachloride (CCl4)-induced acute liver injury in rats.Methods6 groups (n = 6) of rats received oral test solutions: 10% dimethyl sulfoxide (DMSO), 200 mg/kg silymarin, or MEDL (50,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 39 publications
3
51
0
1
Order By: Relevance
“…The results indicated that CCl 4 induced oxidative stress with a significant decrease (p < 0.01) in the activities of liver SOD, CAT and GPx in comparison with the normal control values. In addition, hepatic GSH showed a significant (p < 0.01) decrease while MDA levels significantly (p < 0.01) increased in CCl 4 exposed rats relative to the normal group.…”
Section: Hepatoprotective Activitymentioning
confidence: 90%
See 4 more Smart Citations
“…The results indicated that CCl 4 induced oxidative stress with a significant decrease (p < 0.01) in the activities of liver SOD, CAT and GPx in comparison with the normal control values. In addition, hepatic GSH showed a significant (p < 0.01) decrease while MDA levels significantly (p < 0.01) increased in CCl 4 exposed rats relative to the normal group.…”
Section: Hepatoprotective Activitymentioning
confidence: 90%
“…The vehicle (Tween 80), silymarin and S. villosa extract were dosed orally for 7 days. On the 7th day, hepatotoxicity was induced in rats of groups II -V using 1 mL/kg of CCl 4 (50 % solution in olive oil) by intraperitoneal route [4], while rats of Group I were injected with an equal volume of olive oil.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
See 3 more Smart Citations